An interpretative phenomenological analysis of the development and maintenance of gluten‐related distress and unhelpful eating and lifestyle patterns in coeliac disease. Issue 3 (15th February 2022) - Satherley, Rose‐Marie; Lerigo, Fiona; Higgs, Suzanne; Howard, Ruth
Abstract : Objective: Estimates indicate that individuals with coeliac disease are more likely to experience disordered eating and impaired well‐being than healthy controls, but less is known about the mechanisms by which these factors are related. The aim of this study was to understand experiences of coeliac disease and influence on subsequent unhelpful eating and lifestyle patterns. Methods: An online focus group discussion, hosted through a synchronous chat log, with adults living with coeliac disease was conducted. Seven individuals discussed their condition, lifestyle, and dietary changes post‐diagnosis. Discussions were analysed using an interpretative phenomenological approach, a technique that enables new practical or research insight into health conditions based upon participants' experiences of their condition. Results: Three themes were identified: (i) Nobody knew what was happening to my body; (ii) I am so afraid of being 'glutened' that it is central to my thoughts and anxieties; and (iii) I am frightened but I can keep myself safe by being a 'good' coeliac. These appeared to contribute to participant distress or unhelpful eating or lifestyle behaviours. Participants appeared to develop severe anxiety around gluten, and implausible beliefs around diet and lifestyle management that appear to initiate and maintain unhelpful eating behaviours and maladaptive lifestyles changes, that contribute to distress. Conclusions: Extending current knowledge, we propose a novel cognitive perspective on the development and maintenance of disordered eating in coeliac disease. Implications for how health providers can better support individuals with coeliac disease, and the role of dietary management, anxiety, and gastrointestinal symptoms in the development of disordered eating are discussed.